Nos gramados do Sul: A seleção baiana de futebol e o torneio do Centenário da Independência em 1922 - Dos Santos, Henrique Sena [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2012)
This article aims to understand how the participation and performance of the state of Bahia at the I Campeonato Brasileiro de Seleções (I Brazilian Soccer Championship), also known as the Torneio do Centenário (Centenary Championship) in 1922 represented an opportunity for the state to claim a centrality in the formation of a national identity associated with soccer. The tournament was conceived as a draft for the formation of a national soccer team that would participate in the VI Campeonato Sul Americano (VI South American Championship) in Brazil. In addition, the event also came to be regarded as a celebration of the fi rst centenary of the Independence, a date that has encouraged the country to refl ect upon its national identity, as well as to reconsider its insertion in modernity. Bahia did well in the tournament, ensuring the second position. As a result, the local press went on to claim the participation of their athletes in the national team and to criticize the disregard of the states of Rio de Janeiro and São Paulo towards the Northern region of the country. The local press would also challenge the policies of the Confederação Brasileira de Desportos (Brazilian Sports Confederation), the CBD, claiming that they favored the Southern states. Moreover, for the local elites the success of Bahia in the tournament represented the strength and greatness of the state, which gave them the right to claim a greater space and role in the destiny of the country. Finally, the performance of Bahia and its consequences have allowed us to question the limits and peculiarities of the formation of a national identity through the sport, at a moment when the country sought to rethink their identity historically marked by disputes and regional tensions.
In the Southern fields: The Bahia state soccer team and the Centenary of Independence championship of 1922
Keywords: Bahia; Centenary of Independence; Identity; Soccer